2003
DOI: 10.1182/blood-2002-09-2684
|View full text |Cite
|
Sign up to set email alerts
|

RANK ligand and osteoprotegerin in myeloma bone disease

Abstract: Osteoclasts as effector cells in skeletal malignanciesSkeletal complications represent frequent and significant events in patients with multiple myeloma, and include osteolytic lesions, pathologic fractures, neurologic symptoms (pain, paralysis), and profound hypercalcemia. 1,2 At the cellular level, these complications are due to an excessive growth of malignant myeloma cells within the bone marrow microenvironment and their interactions with osteoblastic and osteoclastic lineage cells. 1,3,4 A consistent his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0
14

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(154 citation statements)
references
References 53 publications
(72 reference statements)
2
135
0
14
Order By: Relevance
“…12 The imbalance in RANKL (receptor activator of nuclear factor kappaB ligand)-toosteoprotegerin ratio in the bone marrow microenvironment is a crucial mechanism leading to osteoclast activation. 13 The increased bone resorption can be measured by various collagen type-I degradation markers. 14 In various studies, it was shown that serum carboxy-terminal telopeptide of type-1 collagen (ICTP) is a sensitive and specific marker of increased bone resorption [15][16][17] and has a prognostic impact for overall survival (OS) in MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…12 The imbalance in RANKL (receptor activator of nuclear factor kappaB ligand)-toosteoprotegerin ratio in the bone marrow microenvironment is a crucial mechanism leading to osteoclast activation. 13 The increased bone resorption can be measured by various collagen type-I degradation markers. 14 In various studies, it was shown that serum carboxy-terminal telopeptide of type-1 collagen (ICTP) is a sensitive and specific marker of increased bone resorption [15][16][17] and has a prognostic impact for overall survival (OS) in MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis is that SH-SY5Y cells could have the capability of neutralizing OPG, as already described for other tumors. 29 Some authors have demonstrated that myeloma cells adopt mechanisms to inhibit the production of OPG or its availability in the bone microenvironment. Syndecan-1, a proteoglycan heparan sulfate expressed on the membrane of myeloma cells, binds inactive OPG by the same binding domain as heparin; then, OPG is internalized and degraded by lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other cell sources for RANKL in addition to osteoblasts in myeloma include T lymphocytes 15 as well as myeloma cells themselves, which have been reported to express low levels of RANKL. [16][17][18][19] Pearse and co-workers 20 were the first to clearly demonstrate that RANKL expression was upregulated in bone marrow biopsies in patients with myeloma while OPG was decreased. They detected RANKL expression in cells in the marrow microenvironment rather than the myeloma cells.…”
Section: Osteolytic Factors Produced or Induced By Myeloma Cellsmentioning
confidence: 99%